Potential Role of Seaweed Polyphenols in Cardiovascular-Associated Disorders - Manuel Gómez-Guzmán; Alba Rodríguez-Nogales; Francesca Algieri; Julio Gálvez (Marine Drugs, 2018)
The beneficial effects of various polyphenols with plant origins on different cardiovascular-associated disorders, such as hypertension, diabetes mellitus type 2 and metabolic syndrome are well known. Recently, marine crude-drugs are emerging as potential treatments in many noncommunicable conditions, including those involving the cardiovascular system. Among the active compounds responsible for these activities, seaweed polyphenols seem to play a key role. The aim of the present review is to summarise the current knowledge about the beneficial effects reported for edible seaweed polyphenols in the amelioration of these prevalent conditions, focusing on both preclinical and clinical studies. This review will help to establish the basis for future studies in this promising field.